Interleukin-15 and creatine kinase response to high-intensity intermittent exercise training - dos Santos, Thaislaine [UNESP]; Lira, Fabio Santos [UNESP]; Antunes, Barbara Moura [UNESP] (Springer Nature, 2020)
Purpose: To verify the acute and chronic effects of high-intensity intermittent training (HIIT) on interleukin 15 (IL-15) response and the relationship between circulating IL-15 concentrations and muscle damage in young men. Methods: Physically active men performed two different training protocols at moderate and high intensity, three times per week for 5 weeks. Twenty subjects were randomly allocated into high-intensity intermittent training group (HIIT-5 km 1 min at 100% of maximal aerobic speed interspersed by 1 min passive recovery; n = 10) or moderate-intensity continuous training group (MICT-5 km 70% of maximal aerobic speed; n = 10). An acute exercise session was performed with blood sample collection pre-exercise, immediately post-exercise, and 60 min post-exercise (before and after 5 weeks of training). Blood samples were used to analyze serum IL-15 and creatine kinase (CK) concentrations. Results: The results showed no changes in serum IL-15 concentrations independent of protocol, moment measurement, and intervention period. CK concentrations showed higher values post-exercise when compared to pre-exercise in both protocols. No significant relationship was found between serum IL-15 and CK concentrations. Conclusion: Our findings point to the absence of acute and chronic changes in serum IL-15 concentrations in response to 5 weeks of high-intensity intermittent training. In addition, data suggest that the release of this cytokine is not related to muscle damage in healthy young men.
Keywords: Cytokines; Exercise training; Inflammation; Interleukins; Metabolism